PEMBUATAN GLUKOSA DAN ALKOHOL DARI SAGU (Metroxylon spp.) - Tjutju Nurhayati Syahri; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1988)
A study for  production  of glucose   and  alcohol  from  sago  (Metroxylon Spp)  was conducted   on a  laboratory  scale in  the  Forest  Product Research and  Development Centre, Bogor.Treatment condition given  for hydrolysis of  sago in order   to produce   glucose  was three  levels of  sulfuric  acid  (of 0.5 N; 0,75 N and 1.0 N)  with  three levels of  temperature and pressure  (of 250°F/15psi, 259°F/20psi,  and 274oF/30psi).The  reaction time  for hydrolysis at  each  treatment combination were three levels  (of  90  minutes, 120  minutes and 150 minutes). Glucose obtained from sago hydrolysis   in this experiment  was then  fermented for producing  alcohol  by means of  Sacharomyses cereuiciae  enzym   activity    from  yeast.The  result  showed   that  glucose  yield   during  these experiment  ranged  from 42.8 to  77,6  percent. The  maximum glucose  yield is obtained from the 274°F/30psi treating  condition   and  sulfuric  acid concentration of  1.0 N  within 120 minutes of  hydrolysis time.  Until 120  minutes   of  hydrolysis  period   the glucose  yield  tend  to increase with  the increasing treatment   combination level.   The  results  of glucose tends to  decrease afterwards  at hydrolysis  period  of 1.50 minutes.The highest  alcohol  yield  is 14.2  percent and is obtained  from  fermentation  of highest  glucose yield of 77.6 percent. Based on the result of chromatographic analysis  of alcohol  revealed  that alcohol produced is classified cu. ethanol  (C2H50H)